(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Innovations are essential for businesses to stay competitive, adapt to changing market conditions, and drive growth. By embracing innovation and fostering a culture of creativity and experimentation, businesses can unlock new opportunities, solve complex problems, and create value for customers, employees, and stakeholders. The article discusses the essence of innovation, the main types of innovation, analyzes and presents the importance of innovation in business promotion.